The Effect of The Two Stay Two Stray Learning Model Assisted by the Wizer.Me Application on the Problem-Solving Ability of Grade XI Students - Triyas Sayekti; Aura Nawamadani Amrah (International Journal of Research in Mathematics Education, 2025)
This study aims to determine the effect of the Two Stay Two Stray (TSTS) learning model assisted by the Wizer.me application on the mathematical problem-solving abilities of class XI students at a vocational school in Banyumas Regency. This study was motivated by the low ability of students in solving mathematical problem-solving problems. This study uses a quantitative approach with a quasi-experimental design method of the Nonequivalent Control Group Design type. The subjects of the study consisted of two classes, namely the experimental class using the TSTS model assisted by Wizer.me and the control class using conventional learning methods. Each class consists of 25 students. The instruments used in this study were pretest and posttest essay tests arranged based on problem-solving indicators according to Polya. Data analysis techniques used normality, homogeneity, t-test, and N-Gain tests. The results of the t-test showed that there was a significant difference between the posttest scores of the experimental class and the control class, with a significance value of 0.000 <0.05. In addition, the average value of N-Gain in the experimental class was higher than that of the control class. Based on these results, it can be concluded that the TSTS learning model assisted by the Wizer.me application has a positive effect on improving students' mathematical problem-solving abilities.Keywords: Problem Solving, Two Stay Two Stray, Wizer.me, Mathematics